2016
DOI: 10.1073/pnas.1608520113
|View full text |Cite
|
Sign up to set email alerts
|

Exon skipping of FcεRIβ eliminates expression of the high-affinity IgE receptor in mast cells with therapeutic potential for allergy

Abstract: Allergic diseases are driven by activation of mast cells and release of mediators in response to IgE-directed antigens. However, there are no drugs currently available that can specifically down-regulate mast cell function in vivo when chronically administered. Here, we describe an innovative approach for targeting mast cells in vitro and in vivo using antisense oligonucleotide-mediated exon skipping of the β-subunit of the high-affinity IgE receptor (FceRIβ) to eliminate surface high-affinity IgE receptor (Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 47 publications
1
33
0
Order By: Relevance
“…The reason why these patients show almost undetectable levels of basophil FcεRI receptor is not yet fully understood. Genetic variability in the FcεRI receptor could be a plausible explanation, since recent studies have shown that experimental molecular changes in the subunits of this receptor can affect its expression on the cell surface (36). Other authors have also observed basopaenia in patients with more active CSU disease (37,38), which reflects the recruitment of basophils to skin tissue and might lead to decreased expression of FcεRI receptor on peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…The reason why these patients show almost undetectable levels of basophil FcεRI receptor is not yet fully understood. Genetic variability in the FcεRI receptor could be a plausible explanation, since recent studies have shown that experimental molecular changes in the subunits of this receptor can affect its expression on the cell surface (36). Other authors have also observed basopaenia in patients with more active CSU disease (37,38), which reflects the recruitment of basophils to skin tissue and might lead to decreased expression of FcεRI receptor on peripheral blood.…”
Section: Discussionmentioning
confidence: 99%
“…In the first of these articles, a recently identified technique referred to as exon skipping has been specifically applied to target and downregulate IgE receptor expression on mast cells. 110 This approach affects specifically the mast cell/basophil compartment, unlike use of tyrosine kinase inhibitors that target receptors or pathways present in multiple cell types. This approach used antisense oligonucleotidemediated exon skipping of the b-subunit of FcεRI to eliminate surface expression of FcεRIb, which in turn eliminates surface expression of FcεRI.…”
Section: New Interventions That Alter the Mast Cell Compartmentmentioning
confidence: 99%
“…This approach worked in vivo, as shown in mouse models of IgE-dependent allergic dermatitis. 110 Another novel approach depended on engineering a mechanism-based SCF partial agonist. 111 Normally, SCF is a growth factor that acts through KIT to promote hematopoietic progenitor cell expansion.…”
Section: New Interventions That Alter the Mast Cell Compartmentmentioning
confidence: 99%
“…Morpholino oligomers bind mRNA and either block translation or modify pre-mRNA splicing and induce exon skipping ( 252 ). This approach has recently been demonstrated in mice showing that morpholinos targeting the FcεRI β-subunit decreased IgE receptor expression and function on mast cells and basophils ( 240 ) and was beneficial in treating a mouse model of allergic dermatitis. Morpholino-based therapy is approved for Duchenne muscular dystrophy ( 243 , 244 ), suggesting that this approach can succeed.…”
Section: Therapeutics Targeting Mast Cellsmentioning
confidence: 99%